Однобайтові палітрові графічні формати для зберігання цифрових кольорових зображеннь - Загребнюк, Виктор Иванович; Кумиш, В. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Two bitmap image formats that use independent adaptive palette for every single image are developed. They provide image compression in more than 3 times and save the high image quality